Gender dan Budaya: Citra Perempuan pada Cerpen “Perempuan Itu Pernah Cantik” karya Mashdar Zainal - Mazidah, Nadia Nur; Zarnubi, Muhammad; Surur, Misbahus (Deskripsi Bahasa, 2026)
In married life, women often experience a significant transition that can leave them in shock. This study aims to describe the portrayal of women in the household in the short story "Perempuan Itu Pernah Cantik " by Mashdar Zainal and to examine the cultural elements that influence this portrayal. The analysis of women's images and cultural aspects is conducted using critical discourse analysis by Sara Mills and Ruth Wodak. The research employs a qualitative method. The findings reveal that the portrayal of women and cultural elements in "Perempuan Itu Pernah Cantik " remains highly relevant to contemporary women's lives and contributes to many household disputes. According to Sara Mills' perspective, the portrayal of women in the short story is categorized into six images: women associated with beauty; women who seek validation and praise; women who prioritize emotions; women who are dependent on men; women with maternal instincts; and women who compare their single life with their married life. Furthermore, according to Ruth Wodak, the cultural elements shaping the image of women in the short story fall into three categories: the culture of women as managers of domestic affairs, the culture of women as gentle, and the culture that considers child-rearing a woman's duty.